TINJAUAN PUSTAKA TENTANG PRINSIP TAUHID DAN KEADILAN DALAM HUKUM EKONOMI SYARIAH: LANDASAN TEORETIS DAN IMPLIKASINYA TERHADAP PRAKTIK EKONOMI MODERN - Rulyjanto Podungge; Al-Amin (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study aims to examine in depth the principles of tawhid and justice as theoretical foundations in Islamic economic law and their implications for modern economic practices. Through a literature review, it was found that the integration of tauhid and justice creates an economic paradigm that is not only oriented towards material well-being but also spiritual well-being. Tauhid emphasises that all economic activities must be based on an awareness of the oneness of Allah and moral responsibility, while justice demands equitable distribution of wealth, transparency, and protection of the rights of all parties. This study also identifies challenges in implementing Islamic economics in the modern era, such as low public literacy, regulatory limitations, and the dominance of conventional systems. However, there are also significant opportunities through education, technological innovation, and the strengthening of policies based on Islamic values. Thus, Islamic economics has the potential to address global economic inequality and moral crises through the integration of the principles of tauhid and justice into modern economic practices.